IMPLEMENTASI KADER YOUNG MOBILE POSBINDU UPAYA PROMOTIF DAN PREVENTIF PENYAKIT TIDAK MENULAR - Fitriah Fitriah; Mustofa Haris (STIKES NGUDIA HUSADA MADURA, 2021)
The implementation of this community service aims to increase promotive and preventive activities in an effort to prevent non-communicable diseases through PTM young mobile posbindu activities. Previously, PTM Posbindu activities in Rosep Village had not run optimally with low visits during activities. Meanwhile, in Rosep Village, hypertension cases are very high. This community service activity is carried out in September - October 2021. The focus of this community service activity is to increase posbindu activities with a walking posbindu approach with local village youth as cadres. Teenagers are trained to understand about posbindu, young mobile posbidu and detection of PTM risk factors. In addition, youth who have joined the PTM young mobile posbindu cadre are trained to be skilled in PTM risk detection including checking height and weight, blood pressure, blood sugar, cholesterol and gout. Furthermore, adolescents are deployed to the community to move into the community to detect PTM risk factors. As a result, adolescents have the ability to detect risk factors and many people who are detected are at risk of developing PTM. This activity went smoothly, teenagers and the community were very enthusiastic to apply these skills in the detection of PTM risk factors.